2019
DOI: 10.1101/743856
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Severe Hyposmia Distinguishes Neuropathologically Confirmed Dementia with Lewy Bodies from Alzheimer’s Disease Dementia

Abstract: AbstractDue to the absence of core clinical features, many subjects with neuropathologically-confirmed dementia with Lewy bodies (DLB) are never diagnosed as such during life. Most of these are diagnosed with Alzheimer’s disease dementia (ADD) or unspecified dementia. Unrecognized DLB therefore is a critical impediment to clinical studies and treatment trials of both ADD and DLB. There are numerous published studies that suggest that olfactory function tests may be able to diff… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…Hyposmia is likely to begin at prodromal disease stages as it is present in subjects with incidental Lewy body disease and often predates the appearance of motor features. [1][2][3][4][5][6][7][8] On the contrary, patients with clinically determined progressive supranuclear palsy (PSP) have been reported to have normal olfaction. [9][10][11][12][13] However, there is a lack of studies performed regarding pathological confirmation of disease state.…”
Section: Supporting Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Hyposmia is likely to begin at prodromal disease stages as it is present in subjects with incidental Lewy body disease and often predates the appearance of motor features. [1][2][3][4][5][6][7][8] On the contrary, patients with clinically determined progressive supranuclear palsy (PSP) have been reported to have normal olfaction. [9][10][11][12][13] However, there is a lack of studies performed regarding pathological confirmation of disease state.…”
Section: Supporting Datamentioning
confidence: 99%
“…Previous studies have shown that hyposmia is a feature of idiopathic Parkinson's disease (PD) and dementia with Lewy bodies (DLBs). Hyposmia is likely to begin at prodromal disease stages as it is present in subjects with incidental Lewy body disease and often predates the appearance of motor features 1‐8 . On the contrary, patients with clinically determined progressive supranuclear palsy (PSP) have been reported to have normal olfaction 9‐13 .…”
mentioning
confidence: 99%
“…Similarly, up to one-half of subjects with dementia and Parkinson's disease [95][96][97][98][99][100][101][102][103][104][105][106][107] and three-quarters or more of those with DLB, have clinically significant AD pathology [108][109][110][111]. In the great majority of subjects with both ADD and LBD, this co-existence is recognized only at autopsy [41,[112][113][114][115], currently preventing, except for the minority with clinically-typical DLB, the exclusion or stratification of LBD subjects within ADD clinical trials.The presence of LBD in ADD is clearly of clinical significance. Multiple autopsy-validated studies have indicated that cognitive decline is faster in ADD with any degree of associated LBD [26,[42][43][44][45].…”
mentioning
confidence: 99%